The silence of the lambs - Forshaw, Barry (Devil's advocates., 2013)
The 1991 film The Silence of the Lambs, based on Thomas Harris's bestseller, was a game-changer in the fields of both horror and crime cinema. FBI trainee Clarice Starling was a new kind of heroine, vulnerable, intuitive, and in a deeply unhealthy relationship with her monstrous helper/opponent, the serial killer Hannibal Lecter. Jonathan Demme's film skillfully appropriated the tropes of police procedural, gothic melodrama and contemporary horror and produced something entirely new. The resulting film was both critically acclaimed and massively popular, and went on to have an enor.